Applying the Theory of Gendered Organizations to the Lived Experience of Women with Established Careers in Academic Medicine. Issue 5 (19th October 2020) - Balmer, Dorene F.; Courts, Kelly A.; Dougherty, Bridget; Tuton, Lucy Wolf; Abbuhl, Stephanie; Hirshfield, Laura E.
Abstract: Phenomenon: The number of women who enter medical school has been on par with the number of men for almost 20 years, but parity in training has not translated to equity in professional life. To capitalize on the perspective of women faculty with established careers in academic medicine and to bring theory to the largely descriptive research on gender inequity in academic medicine, the authors used the Theory of Gendered Organizations to demonstrate how academic medical centers function as inherently gendered organizations. Approach: The authors recruited women faculty with established careers at one academic medical center based on purposeful and snowball sampling and interviewed 30 participants in Summer/Fall 2018. They coded and analyzed data inductively. In later stages of analysis they used sensitizing concepts from the Theory of Gendered Organizations to guide our focus on formal expectations of, and informal interactions in, the academic medical center. Findings: The disjuncture, i.e., "lip service", between formal expectations intended to be gender-neutral and informal interactions that advantaged men demonstrated how the academic medical center functioned as a gendered organization. Participants experienced these interactions as being treated differently than men and/or being stereotyped. As their careers progressed, participants recognized gender inequity as embedded in the organization, or as they said, "the way things were stacked". Subsequent to this recognition, they navigated this gendered organization by advocating for themselves and younger women faculty. Insights: Women with established careers in academic medicine experienced gender inequity as embedded in the organization but navigate gendered interactions by advocating for themselves and for younger women. Using the Theory of Gendered Organizations as an analytic lens demonstrates how academic medical centers function as gendered organizations; these findings can inform both theory-based research and pragmatic change strategies.